New territorialities against the mega-mining: the case of the Junin’s Comunity Reserve - Murillo Martín, Diana Carolina (2017)
In this article we study a social conflict case related to a large-scale mining project in Ecuador (in the so-called Intag area), from a mixed critical geography and political ecology perspective. We intend to address to what extent this two-decades-long conflict led to significant changes in the territorialities in the area. We interpret the creation of the Junin’s Comunity Reserve as a re-territorialization process, led by surrounding communities, threatened by the territoriality that try to impose transnational “megamining” capitals. The study evidences the relevance of the concept of “de-re-territorialization” coined by Haesbaert. We think that it also shows that, in the context of an accelerated conversion of Latin American territories to the logic of transnational capital, the sequential dynamics “des-“ and then “re-“territorialization by a national or transnational actor is not systematic. It indicates instead, that this conversion is a contradictory process in which antagonistic territorialities are embodied.